Alleviating occupational stress in Chinese junior high school teachers: the role of mindfulness-based interventions - Bian, Huimian; Jiang, He (Frontiers in Psychology, 2025)
IntroductionOccupational stress is a significant issue among junior high school teachers in China, contributing to negative outcomes such as reduced mental health, impaired coping abilities, and decreased job satisfaction.MethodsThis quasi-experimental study investigates the impact of mindfulness-based interventions on occupational stress and mental health among junior high school teachers in China. A total of 118 teachers participated in the study, with a randomly assigned experimental group undergoing an 4-week mindfulness training program, while the control group received no intervention. Standardized measures of occupational stress, mental health, coping self-efficacy, and mindfulness were used to assess the outcomes before and after the intervention.FindingsThe findings revealed that teachers who participated in the mindfulness program experienced significant reductions in occupational stress and improvements in mental health and coping self-efficacy compared to the control group. Additionally mindfulness levels increased significantly among participants who underwent the training.DiscussionThe results suggest that mindfulness-based interventions can effectively alleviate occupational stress and enhance psychological wellbeing among junior high school teachers in China, highlighting the importance of implementing such programs to support educators in managing stress and maintaining mental health.